INFLUENCE OF POLYSULFONAMIDE TANLON FIBER ON RESISTANCE INDICATOR OF POLYTHETRAFLUORETHYLENE - Kalinichenko, Serhii Volodymyrovych; Tomina, Anna – Mariia Vadimivna; Burya, Olexandr Ivanovich; Nachovnyi, Illia Ivanovich (Problems of Friction and Wear, 2021)
The article considers the effect of Tanlon T700 polysulfonamide fiber on the wear resistance of polytetrafluoroethylene under conditions of friction without lubrication. It is established that the introduction of the filler leads to an intensive reduction in wear of the original polymer (486-1215 times), reaching a minimum at a fiber content of 15 mass.%. These results are due to the fact that in the process of friction of the developed polymer composite materials a transfer film is formed on the counterbody: the wear products are fixed in the micro-irregularities of the counterbody; as a result its roughness is reduced. With regard to the coefficient of friction, it was found that the introduction of polysulfonamide fiber reduces this idicator by 15%, reaching minimum values at a filler content of 5-15 mass.%. Further increase in the fiber content (up to 35 mass.%) leads to a sharp increase in the coefficient of friction, due to the high frictional characteristics of the filler. It is determined that the effective content of filler in the polymer matrix is 15 mass.%. Consequently, this composite was recommended for the manufacture of plain bearings of friction units as a coating for rollers of the roller conveyor of the extrusion line of aluminum profile.